CEO Capital: A Guide to Building CEO Reputation and Company Success - Gaines Ross Leslie (American : Wiley, 2002)
Review
"This is an excellent book of dos and don'ts for CEOs, potential CEOs and especially for the PR people who must help them get their message out to their various publics." (Public Relations Quarterly, Summer 2003)
The Holmes Report, February 10, 2003
A manifesto supported by compelling original research and informed by intelligent, sympathetic analysis.
Keywords: Real Estate Investment; Real Estate Management; United States; Rental Housing-Management